Reversible crystal-to-amorphous structural transformations and magnetic variations in single end-on azide-bridged MII (M = Mn, Ni) coordination polymers. Issue 3 (18th December 2017) - Lim, Kwang Soo; Song, Jeong Hwa; Kang, Dong Won; Kang, Minjung; Eom, Sunhwi; Koh, Eui Kwan; Hong, Chang Seop
Abstract : Azide-bridged coordination polymers undergo reversible crystal-to-amorphous phase transformations during the hydration–dehydration process. Abstract : M II (M = Mn, Ni) coordination frameworks, singly linked by end-on azide ligands, were prepared by employing the long, flexible spacer ligand, p -XBP4. These two-dimensional layer structures underwent reversible crystal-to-amorphous phase transformations during the hydration–dehydration process. Moreover, the magnetic nature changes from antiferromagnetic to ferromagnetic coupling when moving from Mn to Ni.